Moral Distress and Moral Injury Among Attending Neurosurgeons: A National Survey. Issue 1 (25th July 2022) - Mackel, Charles E.; Alterman, Ron L.; Buss, Mary K.; Reynolds, Renée M.; Fox, W. Christopher; Spiotta, Alejandro M.; Davis, Roger B.; Stippler, Martina
Abstract : BACKGROUND: "Moral distress" describes the psychological strain a provider faces when unable to uphold professional values because of external constraints. Recurrent or intense moral distress risks moral injury, burnout, and physician attrition but has not been systematically studied among neurosurgeons. OBJECTIVE: To develop a unique instrument to test moral distress among neurosurgeons, evaluate the frequency and intensity of scenarios that may elicit moral distress and injury, and determine their impact on neurosurgical burnout and turnover. METHODS: An online survey investigating moral distress, burnout, and practice patterns was emailed to attending neurosurgeon members of the Congress of Neurological Surgeons. Moral distress was evaluated through a novel survey designed for neurosurgical practice. RESULTS: A total of 173 neurosurgeons completed the survey. Half of neurosurgeons (47.7%) reported significant moral distress within the past year. The most common cause was managing critical patients lacking a clear treatment plan; the most intense distress was pressure from patient families to perform futile surgery. Multivariable analysis identified burnout and performing ≥2 futile surgeries per year as predictors of distress ( P < .001). Moral distress led 9.8% of neurosurgeons to leave a position and 26.6% to contemplate leaving. The novel moral distress survey demonstrated excellent internal consistency (Cronbach alpha = 0.89). CONCLUSION: We developed a reliable survey assessing neurosurgical moral distress. Nearly, half of neurosurgeons suffered moral distress within the past year, most intensely from external pressure to perform futile surgery. Moral distress correlated with burnout risk caused 10% of neurosurgeons to leave a position and a quarter to consider leaving.